ANALISIS MATERI SULIT DIPAHAMI DAN MISKONSEPSI MAHASISWA DALAM MATA KULIAH KALKULUS INTEGRAL - Dona Fitriawan; Romal Ijuddin; Silvia Sayu (Jurnal Numeracy, 2022)
This study aims to analyze and describe what materials are difficult in calculus courses and also materials that are misconceptions. This research was conducted to improve the competence of students in the future. The formulation of the problem in this study is "How to improve student competence in integral calculus courses?" The sub-problems are: 1) What materials do students have misconceptions in integral calculus courses? 2) What materials are difficult for students to understand in integral calculus courses? The research method used is descriptive qualitative by surveying students of Mathematics Education, Faculty of Teacher Training and Education, Tanjungpura University. From the overall results, there were 22 students (60%) did not experience misconceptions and 14 students (40%) experienced misconceptions in the first concept. In the second concept, 40% did not experience misconceptions and 60% of students experienced misconceptions. For the third concept, 70% of students experienced misconceptions and 30% of students did not experience misconceptions. In the fourth concept, 28% of students experienced misconceptions and 72% of students did not experience misconceptions. For the fifth concept, 6% of students experienced misconceptions and 94% of students did not experience misconceptions. And for the sixth concept there are 28% of students experiencing misconceptions and 72% of students not experiencing misconceptions.